Przegląd wybranych modeli różnic indywidualnych w skalowaniu wielowymiarowym - Zaborski, Artur (Review of Selected Individual Differences Models in Multidimensional Scaling, 2007)
The paper presents three individual differences models that make possible to obtain a group stimulus space, individual configurations and subject space (space of weights). Especially the paper refers to:• the weighted Euclidean model in which stimulus space, individual configurations and subject space can be found directly from the set of m proximity matrices,• model INDSCAL based on the scalar-product matrix,• model PINDIS in which individual differences of respondents are found by comparing individual configurations using the Procrustes analysis.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Ekonometria (18); 2007; nr 1151, s. 9-18